Understanding key performance indicators for breast support: An analysis of breast support effects on biomechanical, physiological and subjective measures during running. Issue 9 (3rd May 2017) - Risius, Debbie; Milligan, Alexandra; Berns, Jason; Brown, Nicola; Scurr, Joanna
ABSTRACT: To assess the effectiveness of breast support previous studies monitored breast kinematics and kinetics, subjective feedback, muscle activity (EMG), ground reaction forces (GRFs) and physiological measures in isolation. Comparing these variables within one study will establish the key performance variables that distinguish between breast supports during activities such as running. This study investigates the effects of changes in breast support on biomechanical, physiological and subjective measures during running. Ten females (34D) ran for 10 min in high and low breast supports, and for 2 min bare breasted (2.8 m·s −1 ). Breast and body kinematics, EMG, expired air and heart rate were recorded. GRFs were recorded during 10 m overground runs (2.8 m·s −1 ) and subjective feedback obtained after each condition. Of the 62 variables measured, 22 kinematic and subjective variables were influenced by changes in breast support. Willingness to exercise, time lag and superio-inferior breast velocity were most affected. GRFs, EMG and physiological variables were unaffected by breast support changes during running. Breast displacement reduction, although previously advocated, was not the most sensitive variable to breast support changes during running. Instead breast support products should be assessed using a battery of performance indicators, including the key kinematic and subjective variables identified here.